PERTUMBUHAN TULANG ANAK UMUR 12-26 BULAN PASCA INTERVENSI GIZI - Edwi Saraswati; Basuki Budiman (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2000)
BONE DEVELOPMENT OF CHILDREN 12-26 MONTHS OF AGE AFTER SEVERAL TIME OF INTERVENTION LEFT BEHINDS.Background: In 1998 a study on the effect of three-month high calcium supplementation on bone growth and motor development of children 7-12 months of age had been carried out by the author. The result of the 1998 study showed that bone growth of the supplemented children was 1.5 times better than that of the children who did not receive high calcium supplementation.Objective: To elaborate whether the family whom participated in 1998 study adoptad the intervention scheme (e.g. consumed high calcium supplementation for their children) during economic crisis in Indonesia.Method: A number of 80 out of 100 families who participated in 1998 were able to contacted and were asked participated in 1999 study. The families comprised 41 families comes from treated group and 39 families comes from control group. Child's consumption both qualitative as well as quantitative were collected by interviewed the mother. Qualitative consumption was collected by using 24-hour recall method. Weight and height of the child were measured. Hand and wrist photo X-ray of the child were taken by using portable X-Ray photo HP-300 model to learn the bone growth. The old of the child in the beginning in this study were between 19 and 33 months.Results: The study revealed that bone development in children whom treated high calcium supplemented developed better (1.3 times) than that of children whom were not supplemented. There were changed feeding habit of mother in variation of kinds food especially high calcium food.Recommendations: The age of supplementation program should be given for six months to show a better impact.Key Words: bone-development, cronological age, bone-age, food supplementation